Essential oil composition of wild growing Sage from R. Macedonia - Gjoshe Stefkov; Ivana Cvetkovikj; Marija Karapandzova; Svetlana Kulevanova (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2012)
The main objective of this study was to analyze and identify the essential oil composition of S. officinalis populations growing in Republic of Macedonia and to evaluate these data according to different standards' requirements for, commercially most utilized, Dalmatian sage. The essential oil yield, obtained after hydrodestilation from leaves, of three different populations of Salvia officinalis L. from Republic of Macedonia was determined, varying from 1.40 to 3.46%. The GC/FID/MS analysis of the composition of the essential oils revealed 63, 57 and 51 components in Galicica Mtn., Jablanica Mtn. and Karaorman Mtn. sage populations, respectively. The main components of the oil, in all three samples, were the terpene hydrocarbons, encompassing the monoterpenes: camphor (13.15 - 25.91%), α-thujone (19.25 - 26.33%), β-thujone (2.03 - 5.28%), 1,8-cineole (6.51 - 13.60%), α-pinene (0.93 - 1.47%), borneol (1.07 - 4.67%), then sesquiterpenes: trans (E)-caryophyllene (1.72 - 5.33%), α-humulene (2.89 - 7.99%), viridiflorol (4.27 - 7.99%), and the diterpene manool (2.13 - 3.79%). Thus, our results for the essential oil composition of sage complied with the reference values specified in the DAC 86 monograph for Salvia essential oil.